2014
DOI: 10.1007/s11908-014-0450-9
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Critical Analysis of Serologic Testing for the Diagnosis of Lyme Disease

Abstract: Diagnostic testing for Lyme disease in the clinical setting primarily relies on assessment of serologic responses to infection, with the exception of the early localized phase of disease, in which the diagnosis must be made clinically, due to the recognized insensitivity of serologic testing at this phase of disease. For the diagnosis of early disseminated and late disease, the Centers for Disease Control and Prevention (CDC) recommends a two-tiered approach to testing consisting of initial IgM and IgG quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Her blood smears demonstrated Babesia (figure 1) including some showing classic ‘Maltese cross’ formation as well as confirmatory serological evidence of Lyme disease. The US Centers for Disease Control and Prevention (CDC) recommends a two-step testing approach for the diagnosis of active Lyme disease, which requires confirmation of a positive enzyme immunoassay test (eg, C6 peptide antibody) with IgM and IgG western blot if the patient is less than 30 days from symptom onset or only an IgG western blot for individuals with symptoms greater than 30 days 10. Our patient's Lyme test results were compatible with infection acquired over 30 days.…”
Section: Discussionmentioning
confidence: 64%
“…Her blood smears demonstrated Babesia (figure 1) including some showing classic ‘Maltese cross’ formation as well as confirmatory serological evidence of Lyme disease. The US Centers for Disease Control and Prevention (CDC) recommends a two-step testing approach for the diagnosis of active Lyme disease, which requires confirmation of a positive enzyme immunoassay test (eg, C6 peptide antibody) with IgM and IgG western blot if the patient is less than 30 days from symptom onset or only an IgG western blot for individuals with symptoms greater than 30 days 10. Our patient's Lyme test results were compatible with infection acquired over 30 days.…”
Section: Discussionmentioning
confidence: 64%
“…Sensitivity of serologic testing is poor in early localized disease. Specificity was uniformly excellent in all disease settings at 99% [13,14].…”
Section: Discussionmentioning
confidence: 91%
“…To date all 3 standard tests have 100% sensitivity in late Lyme disease. Over all the positive predictive value and negative predictive value of these tests only make sense when applied with good history, clinical inspection of the patient and the location of occurrence of infection [14,15].…”
Section: Vlse Is a Surface Protein Of B Burgdorferi It Is Encoded Bmentioning
confidence: 99%
“…Diagnostic testing for Lyme disease is traditionally achieved by determination of the serologic responses to B. burgdoferi sensu lato, with the exception of the very early localized phase of disease (EM < 10 days), in which the diagnosis must be done clinically due to the recognized lack of antibody availabe for detection by serologic assays 37 . In this study, we show that we can detect culture confirmed clinically characterized LD using an assay suitable for use at the point of care.…”
Section: Discussionmentioning
confidence: 99%